(untitled) (Journal of the College of Basic Education, 2023)
Nature, silent and mobile, has long been a subject of human interest. For expression and representation, he mixed with it, as he could see it easily. As for the description of nature in Arabic literature, it is not a hadith either. Writers and poets have known Nature did not mix them with it, and many of them became famous as a man of al-Qais, Dhu al-Rama, al-Buhturi and Ibn Rumi and drew inspiration from its manifestations in their similes, representations, and poetic expressions. Clarify their words. Critics searched for nature and described it in Arabic poetry during the literary ages.